Coherent Anti-Stokes Raman Scattering Microscopy and Its Applications - Li, Shaowei; Li, Yanping; Yi, Rongxing; Liu, Liwei; Qu, Junle (Frontiers in Physics, 2020)
Coherent Anti-Stokes Raman Scattering microscopy can provide a high-resolution, high speed, high sensitivity and non-invasive alternative for imaging biomolecules of interest without the need for exogenous labels. In this review, we first introduce the principle of CARS, and then discuss the CARS construction, including laser source and multiplex CARS system, finally introduce the applications of CARS in biomedicine and materials, and prospective for the future.